A global test for phylogenetic signal in shifts in flowering time under climate change. (5th December 2016) - Rafferty, Nicole E.; Nabity, Paul D.
Summary: Shifts in the timing of flowering are a conspicuous biological signal of climate change. These shifts have been documented across the globe for diverse communities. Although many species are flowering earlier, others have exhibited no shifts or delays in flowering. How species respond phenologically will shape interactions both with other community members and with the abiotic environment, altering fitness, abundance and ultimately persistence. To understand if variability in phenological response is influenced by evolutionary history, we tested for phylogenetic signal in shifts in flowering onset for 13 communities representing 116 families across the Northern Hemisphere. We compared the fit of models of neutral evolution (Brownian Motion) with models that incorporate selection (Ornstein–Uhlenbeck). We found significant signal in whether species had shifted and the magnitude of response, with both traits conforming to an Ornstein–Uhlenbeck model of trait evolution. Synthesis . These results show there is global phylogenetic signal in the direction and magnitude of shifts in flowering onset and indicate selection has shaped flowering time responses of related species under climate change; thus, environmentally determined optima may constrain whether and to what degree species respond phenologically to climate change. Our findings further demonstrate the value of testing for phylogenetic signal across multiple communities and comparing multiple models of trait evolution. Abstract : We tested for phylogenetic signal in the direction and magnitude of shifts in flowering onset globally. Our results indicate selection has shaped flowering time responses of related species under climate change; thus, environmentally determined optima may constrain whether and to what degree species respond phenologically to climate change. Our findings further demonstrate the value of testing for phylogenetic signal across multiple communities and comparing multiple models of trait evolution.